(untitled) (Ocean and Coastal Research, 2024)
The Cananéia-Iguape lagoon-estuarine system, where the Ilha Comprida barrier (IC) is located, is one of the most dynamiccoastal areas on the southeastern Brazilian coast. IC island is a 63 km-long barrier and it is limited by the Icapara inletto the north, and the Cananéia inlet to the south. This system has been affected by intense changes in its morphologysince the opening of the Valo Grande artificial channel in 1852 A.D., connecting the nearby Ribeira de Iguape river to theMar Pequeno lagoon. In this context of anthropogenic disturbance on the coastal systems, the objective of this study isto understand the active mechanisms, both natural and anthropogenic, controlling the morphological changes of thenortheastern portion of the IC, from monthly as well as centenary timescales. We analyzed successional addition anderosion of beach ridges using a multi-temporal dataset obtained by Optically Stimulated Luminescence, aerial photos(1962 and 2000), satellite images (1980–2016) and GNSS surveys (2015–2017). The results were compared to climatic(rainfall and waves) data. Northeastward migration rates of the IC ranged from 15.5 m/y, on the GNSS surveys, to 154 m/y,calculated based on OSL rates. Changes on rates on the northeastward inlet migration barrier are related to anthropogenicinterference, mainly the Valo Grande opening and climate changes. Sediment accumulation occurred mainly during thesummer on the baymouth spits. This depositional scheme is consistent with the highest values of Ribeira de Iguape riverflow and the low synergy of waves coming from the South. By contrast, the retrogradation of the coastline occurs inthe winter, when the wave power is stronger than in the summer. This seasonal configuration is controlled both by thebidirectional longshore drift and by the fluvial discharge.